Risk Perception and Preparedness in Flash Flood-Affected Communities: Evidence from Bahorok, Indonesia - Furqan Ishak Aksa; Egianinta Sinulingga (Department of Geography Education, University of Jember, 2022)
The Bahorok River basin has a high flash-flood hazard index. This is shown by loss of lives and damage of homes due to floods in recent years, however, no research examined community preparedness on the hazard of flash-flood. This research aimed to assess the effect of disaster experience and flood-risk perception on disaster preparedness of the people of Bukit Lawang Plantation Village. A cross-sectional survey design was used to determine the relationship between disaster experience, risk perception and preparedness as the independent and dependent variables, respectively. The results showed that disaster experience and risk perception positively and significantly affect the community preparedness. Disaster risk reduction programs in the region only focus on emergency response, rehabilitation, and reconstruction. Furthermore, increasing public awareness and preparedness has not been prioritized in reducing flood risk. This is an essential aspect for consideration because mountainous areas are often marginalized and lack access to disaster risk reduction programs. Keywords : Flood-risk perception; preparedness; flash flood Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License